PENINGKATAN PEMAHAMAN DALAM MATA PELAJARAN IPS MATERI MASA PENDUDUKAN JEPANG DI INDONESIA DENGAN MENGGUNAKAN GAME KOTAK MISTERI PADA KELAS V MI AL-AZHAR GRESIK - Wulandari, Dwi (Journal Of Islamic Elementary School (JIES), 2017)
This research is motivated by the low ability of students to understand the material during the Japanese occupation in Indonesia in class V MI Al-Azhar Gresik, judging from the students' scores on this material which is not satisfactory, because social studies is a subject that tends to cause boredom and in this learning the teacher only using the lecture method. The teacher should be able to process the social studies learning process by combining a game in order to improve the ability to understand the material, namely the Mystery Box Game. There are several problem formulations in this study, namely how students' understanding of the material during the Japanese occupation was applied before the Mystery Box Game was applied, then how the Mystery Box Game was applied to social studies subjects for class V at MI Al-Azhar Gresik, and how to increase students' understanding after it was applied. Mystery Box Game on material during the Japanese occupation of social studies subjects at MI Al-Azhar Gresik. This type of research is classroom action research which is carried out in two cycles, while the CAR model used is the Kurt Lewin model, in which each cycle consists of four stages, including: planning, action, observation and reflection. Data collection techniques were obtained from observation, interviews, documentation, tests and non-tests. The results of his research obtained the results of observations of teacher activities in cycle 1, namely 77% (very good) and in cycle 2 an increase of 93% (very good). Likewise, the student activity in cycle 1 was 78% (very good) and cycle 2 increased to 95% (very good). (2) the increase in understanding of this material can be seen from the average score of students in the pre-cycle which is 60.43 (good) and increases in cycle 1 which is 70.61 (good) and in cycle 2 increases to 80.94 (very good). ). It can also be seen in the increase in the percentage of class completeness in the pre-cycle by 40% (enough) and in the first cycle it increases to 60.86% (good) and in the second cycle it increases by 86.95% (very good).